Solitary-wave propagation and interactions for a sixth-order generalized Boussinesq equation - Bao-Feng Feng; Takuji Kawahara; Taketomo Mitsui; Youn-Sha Chan (International Journal of Mathematics and Mathematical Sciences)
We study the solitary waves and their interaction for a six-order generalized Boussinesq equation (SGBE) both numerically and analytically. A shooting method with appropriate initial conditions, based on the phase plane analysis around the equilibrium point, is used to construct the solitary-wave solutions for this nonintegrable equation. A symmetric three-level implicit finite difference scheme with a free parameter θ is proposed to study the propagation and interactions of solitary waves. Numerical simulations show the propagation of a single solitary wave of SGBE, and two solitary waves pass by each other without changing their shapes in the head-on collisions.